Reconfiguration method of tensegrity units using infinitesimal mechanisms. Issue 6 (8th July 2019) - González, Andrés; Luo, Ani; Shi, Dongyan
Abstract : Purpose: This paper aims to present a reconfiguration strategy for actuated tensegrity structures. The main idea is to use the infinitesimal mechanisms of the structure to generate a path along which the tensegrity can change its shape while maintaining the equilibrium. Design/methodology/approach: Combining the force density method with a marching procedure, the solution to the equilibrium problem is given by a set of differential equations. Beginning from an initial stable position, the algorithm calculates a small displacement until a new stable configuration is reached, and recurrently repeats the process during a given interval of time. Findings: By means of three numerical simulations and their respective experimental example, the efficacy of this algorithm for reconfiguring the well-known three-bar tensegrity prism along different directions is shown. The proposed method shows efficiency only for small changes of string length. Further work should consider the application of this method to more complex tensegrity structures. Originality/value: The advantage of this reconfiguration method is its simplicity for finding new stable positions for tensegrity structures, and the fact that it doesn't need the information of the material of the structure for the computations.